Developing a Model of Financial Reporting Transparency and Accountability in Municipalities - Salarzehi, Hamid; Piri, Habib; Sotudeh, Reza; Haghparast, Abbasali (Management Strategies and Engineering Sciences, 2027)
The purpose of the present study was to develop a model for financial reporting transparency and accountability in municipalities. In terms of its objective, this study is an applied research project, and with respect to its nature, it is a descriptive-survey study. The research was conducted in two stages using a mixed-methods approach (qualitative and quantitative) to design and explain a financial transparency model. To this end, in the qualitative phase, content analysis and a review of the theoretical foundations and previous studies were employed to propose a conceptual framework for measuring transparency. Subsequently, in order to assess and strengthen the validity of the proposed model, the opinions of academic and professional experts were collected through a questionnaire using the Delphi technique. The study sample consisted of 20 auditing experts who participated in the research. The findings indicate that the variables and components extracted from the content analysis of previous literature and those utilized in international research and studies share common elements identified as factors influencing financial transparency in municipalities and other non-governmental public organizations. The results further revealed that the dimensions and components derived from the content analysis of the literature, consistent with the views of experts and the statistical population in Iran, including the social dimension, organizational dimension, economic dimension, and political dimension, each have a significant impact on the financial reporting transparency of municipalities.